2005
DOI: 10.1111/j.1600-0609.2005.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term experience with low‐dose interferon‐α and PUVA in the management of early mycosis fungoides

Abstract: Complete remission (CR) was achieved in 84% and an overall response rate in 98% of cases: six-month CR was associated with a non-confluent skin infiltrate at histology (P = 0.044) and 14-month CR with high epidermal CD1a+ dendritic-cell density (P = 0.030). The combination protocol was successfully tolerated and the most common reason of 'failure' was related to relapse and not to toxicity. Sustained remissions were achieved in 20% of patients. High CD8+ lymphoid T-cell density was associated with a lower rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
2
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 39 publications
(67 reference statements)
0
56
2
4
Order By: Relevance
“…Anfang der 90er-Jahre wurde eine prospektiv angelegte, randomisierte [24]. Basierend auf diesen Daten, gehört die Kombinationstherapie Interferon plus PUVA zu den effektivsten, die für die frühen Stadien des CTCL zur Verfügung stehen [19].…”
Section: Puva In Kombination Mit Interferon Und Bexarotenunclassified
“…Anfang der 90er-Jahre wurde eine prospektiv angelegte, randomisierte [24]. Basierend auf diesen Daten, gehört die Kombinationstherapie Interferon plus PUVA zu den effektivsten, die für die frühen Stadien des CTCL zur Verfügung stehen [19].…”
Section: Puva In Kombination Mit Interferon Und Bexarotenunclassified
“…In this trial disease free survival projected to 48 months was 75% [53]. Subsequently in a multicentric prospective Phase II clinical study on 89 patients with early-stage IA to IIA MF treated for 14 months with low-dose IFN α-2b (6-18 MU/wk) and PUVA, they have been reported that CR was achieved in 84% and an overall response rate in 98% of cases [54]. The treatment was well tolerated and treatment failure due to toxicity was not frequent in the patients.…”
Section: Interferonsmentioning
confidence: 99%
“…Mucosal involvement is uncommon and occurs usually in the form of oral ulcers and gingival hyperplasia whereas genitalia are rarely affected [1] . Among the few cases of WG with…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of MF also varies according to stage of disease. Early-stage MF is highly responsive to topical treatments such as topical chemotherapy, ultraviolet irradiation (psoralen + UVA) and immunomodulatory agents such as interferon and retinoids [1] . However, systemic disease, which requires more aggressive and potentially more toxic therapy such as systemic chemotherapy or total-skin electron beam therapy, may be clinically silent and therefore potentially missed [2] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation